The needs analysis of the marriage education program for Turkish Cypriot community: Development phase - Salman, Nihal; Batman, Kemal Akkan; Sorakin, Yasemin (Frontiers in Psychology, 2022)
This research is a needs analysis to develop a marriage education program to be held in the TRNC. The aim of the research is to compare the views of married and divorced individuals about marriage education and to determine their needs for marriage education. For this purpose, it has been determined in which subjects they see themselves as sufficient or inadequate, in which subjects they are willing to participate in the training and in which subjects they are unwilling. In this study, embedded design, one of the mixed research methods in which qualitative and quantitative methods are used together, was used. The dominant dimension of this study is the qualitative research method, and the supporting dimension is the quantitative research method. In the qualitative aspect of the research, the sample group was studied with 16 married and divorced participants living in the TRNC. In the quantitative dimension, a total of 385 married or divorced participants were consulted using the sample calculation of unknown universe. The findings are as follows; In both quantitative and qualitative dimensions, the majority of the participants think that if marriage education is given, they can have a healthier and happier marriage. Married and divorced individuals, effective communication, ways of conflict resolution, respect for differences in understanding in raising children, the causes and consequences of cheating, the importance and functions of the family, expectations from marriage and spouse, the processes experienced by new couples, attitudes and behaviors that may adversely affect marriage, power balance and marital status. They stated that they wanted to receive training on adjustment, relations with families in marriage, marriage and business life, anger control, coping with violence and prevention, spending habits and its effects on marriage, effects of financial difficulties on marriage, sexual life and problems in marriage. A training program will be developed for these determined subjects and will be applied to 20 participants in a semi-experimental model through the TRNC Ministry of National Education. The marriage psycho-education program to be prepared will be developed on the basis of a cognitive behavioral approach.